2023
DOI: 10.1093/ofid/ofad138
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of Typhoid Intestinal Perforation in Africa: Results From the Severe Typhoid Fever Surveillance in Africa Program

Abstract: Background Typhoid intestinal perforation (TIP) remains the most serious complication of typhoid fever. In many countries, the diagnosis of TIP relies on intraoperative identification, as blood culture and pathology capacity remain limited. As a result, many cases of TIP may not be reported as typhoid. This study demonstrates the burden of TIP in sites in Burkina Faso, Democratic Republic of Congo (DRC), Ethiopia, Ghana, Madagascar, and Nigeria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…In this study, most typhoid intestinal perforations occurred in individuals aged 20-40 years, consistent with the Birkhold study's ndings where over 47.1% of perforations occurred in the 2nd and 3rd decades (15). Chalya et al suggested that the increasing prevalence of typhoid intestinal perforation among this economically active age group in our setting stems from their propensity for adventurous and mobile lifestyles, often leading to the consumption of unhygienic food away from home.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, most typhoid intestinal perforations occurred in individuals aged 20-40 years, consistent with the Birkhold study's ndings where over 47.1% of perforations occurred in the 2nd and 3rd decades (15). Chalya et al suggested that the increasing prevalence of typhoid intestinal perforation among this economically active age group in our setting stems from their propensity for adventurous and mobile lifestyles, often leading to the consumption of unhygienic food away from home.…”
Section: Discussionsupporting
confidence: 90%
“…In Malawi, the seasonality of intestinal perforations mirrored the seasonality of blood culture-confirmed typhoid [9,58]. Similarly, monthly intestinal perforations were significantly correlated with monthly positive S. typhi cultures in a large typhoid surveillance study in six African countries [5]. In the DRC, surgeons also reported an increase in peritonitis cases during a severe outbreak of typhoid fever, putting additional strain on an already overburdened health care system [59], which could be mitigated with TCV introduction.…”
Section: Plos Global Public Healthmentioning
confidence: 84%
“…Typhoid intestinal perforation (TIP) is a late complication of typhoid fever that generally occurs approximately two weeks after initial symptoms [1]. Patients present with fever and non-specific symptoms, such as abdominal pain, rebound tenderness, and vomiting [4,5]. One or more oval anti-mesenteric perforations in the distal ileum, as described in operative reports, is considered pathognomonic for TIP [6,7].…”
Section: Introductionmentioning
confidence: 99%